Craniofacial and dental anomalies among mentally challenged children - Megha Jain; Sudheendra U Shridhar; Sandeep Gupta; T Raju Ragavendra; Sowmya Kasetty (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate the prevalence of craniofacial and dental anomalies among different developmental disorders in mentally challenged subjects of various special schools. Material and Methods : A cross sectional study was conducted in four rehabilitation centers for mentally disabled subjects in Bhopal City. Atotal o f296 subjects with age range of 5-15 years were screened and findings were recorded in specially prepared proforma. Results: Among 296 subjects, 73 were of Down's syndrome (DS), 168 of mental retardation (MR), 31 of autism (AT) and 24 of cerebral Palsy (CP). The anomalies were found to be predominant in syndromic mental disability compared to non-syndromic disorders. High vault palate was the most common developmental anomaly amongst all the four disabilities. Gingivitis & hypersalivation was noted as an additional finding in all the subgroups. Conclusion: Craniofacial and dental anomalies usually supplement mentally challenged children, leading to poor performance of stomatognathic complex. Therefore critical appraisal of oral health status of such subjects is imperative.